Preliminary Validation of the Rey 15-Item Test and Reliable Digit Span in Native Japanese Samples. Issue 5 (October 2019) - Ryan, Joseph J.; Yamaguchi, Takahiro; Kreiner, David S.
The Rey 15-Item Test and reliable digit span were evaluated in Japan. Participants were controls ( n = 15), healthy volunteers instructed to simulate memory impairment ( n = 12; 5 of 17 volunteers did not comply with instructions and were dropped), healthy elderly ( n = 12), and cognitively disabled nursing home residents ( n = 8). On the 15-Item Test, controls and elderly performed similarly and were combined. Nursing home residents could not cope with the 15-Item Test and were dropped. Total score was a fair predictor of dissimulation using a cutoff ≤ 8. Rows were fair predictors using a ≤2 cutoff. Sensitivities were low and specificities were excellent. Reliable digit span contrasts between simulators and each of the other groups demonstrated that reliable digit span discriminated controls and elderly from simulators (≤6 and ≤5 cutoffs). Sensitivities were moderate and specificities were excellent. Reliable digit span did not differentiate simulators from nursing home residents.